Vesigenurtacel-L (HS-410) in the management of high-grade nonmuscle invasive bladder cancer. (December 2016) - Keehn, Aryeh; Gartrell, Benjamin; Schoenberg, Mark P
Unlike other malignancies, the death rate of bladder cancer has not declined in several decades, highlighting the need for new treatment options. In the emerging era of immunotherapy, therapeutic cancer vaccines are an attractive option to cure, control and prevent cancer. Despite this, finding a feasible and efficacious vaccine platform has proven elusive across all malignancies. Vesigenurtacel-L is the first whole cell, allogeneic vaccine intended to treat high-grade, nonmuscle invasive bladder cancer. This type of vaccine technology for bladder cancer is novel, and has the potential to be both economically and logistically feasible.